MANAJEMEN KEPALA SEKOLAH DALAM PENERAPAN BUDAYA SEKOLAH ISLAMI - Arisman Juanda (FITRAH: International Islamic Education Journal, 2022)
The principal who plays a role as a leader in shaping and managing Islamic culture should be carried out optimally, namely full responsibility and sustainability. The purpose of this research is to find out the planning and implementation carried out in the application of Islamic school culture. This research uses a descriptive method with a qualitative approach. Data collection techniques used are: interviews, observation, and documentation studies. The research subjects were school principals, religious teachers, homeroom teachers, and student council presidents as student representatives at Unggul Tunas Bangsa High School in Aceh Barat Daya. The results of the study show that: Islamic school cultural planning is planned in school meetings, there are special programs related to religious events, group schedules for clean Friday, homeroom class note sheets, there are rewards and punishments for those who do and don't. The implementation is by providing motivation to students, support, commitment and collaboration with all school officials so that this can be carried out properly.